Strategic Partnership in the Context of State Relations in Bilateral, Trilateral, and Multilateral Relations from the Perspective of Indonesia's Maritime Security - Sanjaya, Aji (Riviera Publishing, 2024)
As the world's largest archipelagic country with 17,504 islands, Indonesia has significant strategic interests in maintaining maritime security and stability. The vast ocean around Indonesia is a vital international trade route, an important natural resource, and a potential arena for international conflict and cooperation. In this context, the Strategic Partnership, both bilaterally, trilaterally, and multilaterally, plays a crucial role in supporting Indonesia's maritime defense policy. Strategic Partnership in the context of good state relations is a key component in international diplomacy involving bilateral, trilateral, and multilateral interactions. This article aims to explore the dynamics and impact of Strategic Partnership in the context of bilateral, trilateral, and multilateral relations from the perspective of Indonesia's maritime defense. The research method used in this article is a literature study. Literature Study activities collect materials related to research from books, scientific journals, literature, and other publications that are worthy of being used as research sources by describing the data through several expert opinions. Strategic Partnership in maritime defense is a very important instrument for countries to maintain regional security and stability. Countries can build strong and sustainable partnerships by understanding the benefits and challenges.